Endophytic Bacteria from Mimosa pudica L.: Morphological and Biochemical Traits and Biocontrol Activity against Alternaria porri - Mazlina Madjid (Biology, Medicine, & Natural Product Chemistry, 2025)
Shallot (Allium cepa L.) is an important horticultural commodity whose productivity is frequently constrained by purple blotch disease caused by Alternaria porri. Excessive reliance on synthetic fungicides for disease control has raised concerns related to environmental sustainability and pathogen resistance. Endophytic bacteria, which inhabit internal plant tissues without causing harm, represent a promising source of biological control agents. This study aimed to characterize the morphological and biochemical traits and to evaluate the biocontrol activity of endophytic bacteria isolated from Mimosa pudica L. against A. porri. A total of twelve endophytic bacterial isolates were obtained from healthy roots, stems, and leaves of M. pudica using a surface sterilization technique. The isolates exhibited diverse colony morphology and growth characteristics. Biochemical characterization revealed that most isolates were gram-positive, catalase-positive, motile, and capable of starch hydrolysis. Antagonistic activity was evaluated using a dual culture assay on potato dextrose agar. The results demonstrated that several isolates effectively inhibited the mycelial growth of A. porri. Among them, isolates MP5 and MP11 showed the highest inhibitory effects, with growth inhibition percentages of 58.2% and 48.7%, respectively, and were classified as having high antagonistic activity. The strong inhibitory performance of selected isolates suggests their ability to produce antifungal metabolites or to suppress pathogen growth through competitive interactions. Overall, endophytic bacteria isolated from M. pudica, particularly isolates MP5 and MP11, exhibit significant potential as environmentally friendly biological control agents for managing purple blotch disease in shallot cultivation.